Impact of chemical weed management in sugar beet ( Beta vulgaris) on productivity, quality and economics - Monika Grzanka; Łukasz Sobiech; Robert Idziak; Arkadiusz Filipczak; Grzegorz Skrzypczak (Journal of Plant Protection Research, 2023)
Weeds in sugar beet ( Beta vulgaris L.) can contribute to a significant reduction in the root yield. The species composition of these plants is an important factor influencing the competition with crops. The aim of the 2-year field experiment with mixtures of: phenmedipham + ethofumesate + metamitron + quinmerac; ethofumesate + metamitron + metamitron + + quinmerac + triflusulfuron-methyl; phenmedipham + ethofumesate + metamitron + + quinmerac + triflusulfuron-methyl + clopyralid + lenacil, and phenmedipham + ethofumesate + metamitron + quinmerac + triflusulfuron-methyl + clopyralid applied in split doses, microdoses and Conviso Smart technology was to determine the weed species community composition and effectiveness of weed control strategies. The most common species occurring in both years were: Chenopodium album L., Fallopia convolvulus L., and Geranium pusillum L. The communities had the highest values of biodiversity indices in 2020 and lower values in 2021. There were no statistically significant differences in the herbicidal effectiveness of the tested herbicidal technologies over both years of research and for individual main weed species – 95–99%. The use of all herbicide variants contributed to achieving significantly higher yields than untreated treatments, and contributed to an increase in profitability of cultivation, but this result depended on the selected strategy. The presented herbicide solutions were characterized by direct income at a similar level.